Pharmacokinetics of a Once-Daily Oral Dose of Moxifloxacin (Bay 12-8039), a New Enantiomerically Pure 8-Methoxy Quinolone - Sullivan, John T. (American Society for Microbiology, 1999)
The pharmacokinetics, safety, and tolerability of oral moxifloxacin, a new 8-methoxy quinolone, were assessed in a randomized, double-blind, placebo-controlled study in which healthy male and female volunteers received either 400 mg of moxifloxacin once daily (n = 10) or a placebo once daily (n = 5) for 10 days. Plasma moxifloxacin concentrations on days 1 and 10 were measured by high-performance liquid chromatography and fluorometric detection. Standard pharmacokinetic parameters were estimated by noncompartmental methods. Natural logarithmic estimates for each pharmacokinetic variable of each subject were analyzed by a two-way analysis of variance. Hematology, blood chemistry, vital signs, and adverse events were monitored, and electrocardiograms (ECG) were performed. Plasma moxifloxacin concentrations of predicted therapeutic relevance were achieved in this study. For day 1, the mean maximum concentration of drug in serum (C(max)) and the area under the concentration-time curve from 0 to 24 h (AUC(0–24)) were 3.4 mg/liter and 30.2 mg · h/liter, respectively. Corresponding means on day 10 were 4.5 mg/liter and 48 mg · h/liter, respectively. On day 10, the mean elimination half-life was approximately 12 h. Plasma moxifloxacin concentrations exceeded the MIC for Streptococcus pneumoniae throughout the 24-h dosing period. The day 1 and day 10 mean AUC/MIC ratios were 121 and 192, respectively, and the mean C(max)/MIC ratios were 13 and 18, respectively. Moxifloxacin was well tolerated; no clinically relevant changes in the standard laboratory tests, vital signs, or ECG were observed. Pharmacokinetic parameters demonstrated linearity, and estimates of pharmacokinetic/pharmacodynamic ratios (AUC/MIC and C(max)/MIC) indicate that the regimen of 400-mg once daily should be effective for treating a variety of infections. Moxifloxacin was found to be safe and well tolerated in healthy volunteers when it was given as a single daily 400-mg dose for 10 days.